2020
DOI: 10.20944/preprints202009.0230.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

General Assessment of the Operational Utility of National Water Model Reservoir Inflows for Bureau of Reclamation Facilities

Abstract: This work investigates the utility of the National Oceanic and Atmospheric Administration’s National Water Model (NWM) for water management operations by assessing the total inflow into a select number of reservoirs across the Central and Western U.S. Total inflow is generally an unmeasured quantity, though critically important for anticipating both floods and shortages in supply over a short-term (hourly) to sub-seasonal (monthly) time horizon. The NWM offers such information at over 5,000 reservoirs across … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Gauch et al (2020) recently demonstrated that the LSTM can accurately predict water discharge at multiple timescales, such as daily and hourly. In contrast with the US National Water Model (Viterbo et al, 2020), the Multi-TimeScale LSTM (MTS LSTM) showed a considerably smaller performance decrease when predicting hourly instead of daily streamflow. Their approach offers the potential to use LSTMs operationally, ingesting data at different temporal frequencies to produce predictions at a desired resolution.…”
mentioning
confidence: 92%
“…Gauch et al (2020) recently demonstrated that the LSTM can accurately predict water discharge at multiple timescales, such as daily and hourly. In contrast with the US National Water Model (Viterbo et al, 2020), the Multi-TimeScale LSTM (MTS LSTM) showed a considerably smaller performance decrease when predicting hourly instead of daily streamflow. Their approach offers the potential to use LSTMs operationally, ingesting data at different temporal frequencies to produce predictions at a desired resolution.…”
mentioning
confidence: 92%